2022
DOI: 10.3390/polym14173555
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Coarse-Grained Soil Stabilized by Poly (Vinyl Alcohol) Solution and Silica Fume under Wet–Dry Cycles

Abstract: To investigate an environmentally benign stabilizer for coarse-grained soil in southeast Tibet, poly (vinyl alcohol) (PVA) and silica fume were used to improve the geotechnical properties of coarse-grained soil. Unconfined compressive strength (UCS) and wet–dry cycle tests were conducted on prepared samples to evaluate the effect of the additive content and curing age on the strength and durability of coarse-grained soil. The results reveal that the UCS of the samples increased with the additive content of PVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The strengthened members are frequently located in harmful media and severe environments in the service life stage, causing early degradation and performance deterioration [31]. The durability issue under environmental conditions considering monolithic samples has been observed via experimental investigation in many previous studies [32][33][34][35][36][37]. In the technical literature, few studies have also been found that observed the durability issue on composite (repaired) samples under a freeze-thaw cycle [38][39][40], elevated temperature [41][42][43][44][45], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthened members are frequently located in harmful media and severe environments in the service life stage, causing early degradation and performance deterioration [31]. The durability issue under environmental conditions considering monolithic samples has been observed via experimental investigation in many previous studies [32][33][34][35][36][37]. In the technical literature, few studies have also been found that observed the durability issue on composite (repaired) samples under a freeze-thaw cycle [38][39][40], elevated temperature [41][42][43][44][45], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are long-chain molecules that can improve the physical and chemical properties of soil, such as its strength, stability and water retention capacity. Zhao et al used Poly (Vinyl Alcohol) Solution and Silica Fume to enhance the strength of coarse-grained soil [9]. Sodium carboxymethyl cellulose (CMC) can improve the production capacity of saline-alkali soil [10].…”
mentioning
confidence: 99%